Perencanaan Sumber Daya Manusia Untuk Meningkatkan Kinerja Aparatur Sipil Negara - Yulian Jitmau; Rio Pernandez Sinaga; Aditya Padini Syah (Maslahah : Jurnal Manajemen dan Ekonomi Syariah, 2024)
This study aims to analyze the importance of human resource planning (HR) in improving the performance of the State Civil Apparatus (ASN). Given the global demands that require efficient and effective governance, the professionalism of apparatus resources is the main key. Good HR planning ensures that the organization has the right number and quality of employees, who can contribute optimally to the achievement of the organization's strategic goals. The research method used is a literature review by collecting data from various relevant literature sources, including books, magazines, and articles. The results show that effective HR planning enables organizations to identify workforce needs, address employee shortages or surpluses, and ensure that employees have the appropriate skills and competencies.